Dinamika Nilai Tukar Rupiah pada Mata Uang ASEAN: Tinjauan Purchasing Power Parity, Interest Rate Parity, dan International Fisher Effect - Sufiah, Dwi Nur Rahma; Fitriyah, Fitriyah (Universitas Negeri Padang, 2025)
People all across the world now have easier access to comparable goods because to globalization. If we want to keep the economy stable via international commerce, we must take the exchange rate into account. The purpose of this research is to determine how well the theories of International Fisher Effect, Purchasing Power Parity, and Interest Rate Parity explain the volatility of the Rupiah against the currency of ASEAN nations. Finding out how the Rupiah has changed due to interest rate and inflation differentials between Indonesia and other ASEAN nations is the main goal of this research. From 2014 to 2023, this research compares the Rupiah's currency rate, interest rates, and inflation rates to those of ASEAN nations. The Random Effect model, run using the E-Views 12 program, is used in this study's panel data regression analysis. Based on the study's findings, the International Fisher Effect idea makes sense here. However, the other two theories show the opposite results. Thus, this indicates a theoretical deviation that causes the theory to be invalid.